Can individual land ownership reduce grassland degradation and favor socioeconomic sustainability on the Qinghai-Tibetan Plateau?. Issue 89 (November 2018) - Cao, J.J.; Holden, N.M.; Adamowski, J.F.; Deo, R.C.; Xu, X.Y.; Feng, Q.
Highlights: Grasslands were contracted to individual households on the Qinghai-Tibetan Plateau. Two distinct types of privately-owned grassland properties, the individually owned (IPP) and the jointly managed (JPP), developed. The social, economic and ecological consequences of IPP and JPP were reviewed. IPP can cause net losses. JPP should be encouraged in this important socio-economic and environmentally-sensitive region. Abstract: Land degradation neutrality (LDN) was introduced to provide a policy framework to achieve Sustainable Development Goal (SDG) 15. Land use policy and management changes can alter the status of land-based natural capital, and exert an influence on ecosystem functioning and interactions with a socio-ecological system. Over the last 30 years, continued efforts to maintain the socioeconomic sustainability of the Qinghai-Tibetan Plateau (QTP) led to the implementation of a unique ownership policy of individual households that were contracted to use defined grassland properties rather than collective nomadic practices. Two distinct types of privately-owned grassland properties now exist: individual private property (IPP) and jointly managed private property (JPP). The influence of IPP (vs. JPP) on grassland degradation has been the subject of a limited number of studies that are reviewed in this paper to help estimate some baseline indicator values for LDN on the QTP. Grasslands under IPP were more degraded according to soil and vegetation measurements, which were indicative of excessive vegetation removal and trampling due to grazing pressure. This pressure occurred because livestock mobility was limited by the imposed restrictions of fencing. A review of the associated socioeconomic status of this practice suggests that the disruption of social networks by the imposition of property lines between individual households acted to limit cultural transmission and collective benefits, such as the sharing of labour, pasture and food. Moreover, IPP seemed to lack the necessary resilience that is required to support the communities and their livestock. Although studies in the QTP are relatively scarce, research suggests that the notion that grassland contracts would address the region's social, economic and environmental problems should be revisited because there is a significant difference in LDN indicator values for IPP and JPP, and evidence of significant degradation in the decades before the 2015 baseline when the UNCCD adopted LDN and SDGs. Evidence suggests that JPP is a more resilient system, capturing the environmental benefits of nomadism and the socioeconomic benefits of land contracts. Given that some of the grasslands are already contracted to individual households, creative JPP property arrangements should be respected. A reconsideration of whether the not-yet-contracted grasslands should be contracted individually rather than jointly, is required if LDN is to be achieved on the QTP by 2030. If the current policy is maintained, research evidence suggests that JPP should be encouraged, and policy makers should seek better ways of ensuring long-term sustainability and that LDN is achieved to maintain the natural capital and associated ecosystem services of the QTP.